Development of an innovative intravaginal model of probiotic inoculation in dairy ovine flocks: positive effects on the vaginal microbiota, vaginitis and fertility - M. Toquet; J. Gomis; E. Jiménez-Trigos; E. Bataller; M. Barba; A. Sánchez; P. González-Torres; Á. Gómez-Martín (Animal)
In vitro studies have reported the antimicrobial effect of an inoculum (L2) made from commercial probiotic strains of Lactobacillus spp. (Lactobacillus (L.) crispatus, L. brevis and L. gasseri) against some ruminants’ pathogens. However, their possible beneficial effects on controlling the vaginosis caused by the use of intravaginal sponges for oestrus synchronisation have not been evaluated in in vivo models. Therefore, the purpose of this study was to perform an intravaginal double inoculation of this same non-lyophilised (non-freeze-dried) L2 inoculum, in 120 ewes from four dairy commercial ovine flocks using straws similar to those used in artificial insemination. Globally, in the entire study population, the fertility percentage (65%) of the inoculated groups increased by 10% compared to the control groups (55%). Specifically, increases in the percentages of pregnant sheep in flocks 1 and 4 (10.7 and 5.7% respectively; P > 0.05) and flock 3 (27.3%; P < 0.05) were observed in inoculated ewes. Overall, the administration of L2 on the day of intravaginal sponge insertion decreased the number of ewes with vaginitis by 11.13% at the time of sponge removal (T1). In the first flock, the administration of the probiotic positively modulated the microbiota with an increased richness and presence of Lactobacillales accompanied by a reduction in Mycoplasma spp. Genera such as Fusobacterium, Streptobacillus, Campylobacter or Trueperella were linked to the presence of vaginitis at T1. Genera belonging to Lactobacillales, including some genera previously reported to be beneficial for pregnancy, significantly increased at the time of pregnancy diagnosis but significantly decreased at T1. The results of this study suggest that the use of probiotics via intravaginal inoculation as a strategy to positively modulate the microbiota and vaginal inflammation, derived from the use of intravaginal sponges, is also associated with improved fertility. This novel approach could improve animal welfare in oestrus-synchronisation protocols and represents an alternative to the prophylactic use of antibiotics.